C-Reactive Protein is not an Independent Risk Factor for Ventricular Thrombus (Annals of Medical Research, 2021)
None
Keywords: C-Reactive Protein; Left Ventricular Aneurysm; Left Ventricular Restoration; Coronary Revascularization.